Streamlined, automated protocols for the production of milligram quantities of untagged recombinant human cyclophilin-A (hCypA) and untagged human proliferating cell nuclear antigen (hPCNA) using ÄKTAxpress™ - Ludwig, Cornelia (Academic Press, 2010)
We developed streamlined, automated purification protocols for the production of milligram quantities of untagged recombinant human cyclophilin-A (hCypA) and untagged human proliferating cell nuclear antigen (hPCNA) from Escherichia coli, using the ÄKTAxpress™ chromatography system. The automated 2-step (cation exchange and size exclusion) purification protocol for untagged hCypA results in final purity and yields of ⩾93% and ∼5 mg L(−1) of original cell culture, respectively, in under 12 h, including all primary sample processing and column equilibration steps. The novel automated 4-step (anion exchange, desalt, heparin-affinity and size exclusion, in linear sequence) purification protocol for untagged hPCNA results in final purity and yields of ⩾87% and ∼4 mg L(−1) of original cell culture, respectively, in under 24 h, including all primary sample processing and column equilibration steps. This saves in excess of four full working days when compared to the traditional protocol, producing protein with similar final yield, purity and activity. Furthermore, it limits a time-dependent protein aggregation, a problem with the traditional protocol that results in a loss of final yield. Both automated protocols were developed to use generic commercially available pre-packed columns and automatically prepared minimal buffers, designed to eliminate user and system variations, maximize run reproducibility, standardize yield and purity between batches, increase throughput and reduce user input to a minimum. Both protocols represent robust generic methods for the automated production of untagged hCypA and hPCNA.